2016
DOI: 10.1073/pnas.1524629113
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic nucleotide-gated channel 18 is an essential Ca 2+ channel in pollen tube tips for pollen tube guidance to ovules in Arabidopsis

Abstract: In flowering plants, pollen tubes are guided into ovules by multiple attractants from female gametophytes to release paired sperm cells for double fertilization. It has been well-established that Ca2+ gradients in the pollen tube tips are essential for pollen tube guidance and that plasma membrane Ca2+ channels in pollen tube tips are core components that regulate Ca2+ gradients by mediating and regulating external Ca2+ influx. Therefore, Ca2+ channels are the core components for pollen tube guidance. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(115 citation statements)
references
References 62 publications
4
111
0
Order By: Relevance
“…The nature of the activated Ca 2+ ‐permeable channels in our experimental system is as yet unknown, but Ca 2+ ‐permeable channels of the CNGC and GLR families, namely GLR1.2, GLR3.7, and CNGC18, seem to participate in generating the tip‐focused Ca 2+ gradient in PTs (Frietsch et al ., ; Michard et al ., ; Gao et al ., ), as pointed out in our model (Fig. ).…”
Section: Discussionsupporting
confidence: 86%
“…The nature of the activated Ca 2+ ‐permeable channels in our experimental system is as yet unknown, but Ca 2+ ‐permeable channels of the CNGC and GLR families, namely GLR1.2, GLR3.7, and CNGC18, seem to participate in generating the tip‐focused Ca 2+ gradient in PTs (Frietsch et al ., ; Michard et al ., ; Gao et al ., ), as pointed out in our model (Fig. ).…”
Section: Discussionsupporting
confidence: 86%
“…The electrophysiological properties of CNGCs have been tested using heterologous expression systems (Table ). These studies revealed that CNGCs that harbour the GQN, GQG and GQS triplets are selective for Ca 2+ and promote Ca 2+ uptake (Gao et al ., , , ; Wang et al ., ). Some heterologously expressed CNGCs are activated when coexpressed with a Ca 2+ ‐dependent protein kinase, CPK32, implying regulation of their activity by phosphorylation (Zhou et al ., ).…”
Section: Physiological and Structural Characteristics Of Plant Ca2+‐pmentioning
confidence: 99%
“…Gao et al . () recently reported that up to eight different subunits of putative Ca 2+ ‐permeable channels can be expressed at the same time in the PM of an individual plant cell.…”
Section: Physiological and Structural Characteristics Of Plant Ca2+‐pmentioning
confidence: 99%
“…The disruption of AtCNGC18, localized in the subapical membrane, induces male sterility due to defective PT growth (Frietsch et al, 2007). AtCNGC18 was recently shown to drive inward cationic currents activated by cAMP/cGMP in an animal heterologous system (Gao et al, 2016). AtCNGC7, which localizes at the flank of the growing tip, and AtCNGC8 have weaker phenotypes, but the double knockout is male sterile (Tunc-Ozdemir et al, 2013a).…”
Section: Ion Fluxes and Gradients At The Tip: An Electrifying Affair?mentioning
confidence: 99%